2015
DOI: 10.1063/1.4936979
|View full text |Cite
|
Sign up to set email alerts
|

A crude model to study radio frequency induced density modification close to launchers

Abstract: Articles you may be interested inA crude model to study radio frequency induced density modification close to launchers The interplay between radio frequency (RF) waves and the density is discussed by adopting the general framework of a 2-time-scale multi-fluid treatment, allowing to separate the dynamics on the RF time scale from that on the time scale on which macroscopic density and flows vary as a result of the presence of electromagnetic and/or electrostatic fields. The focus is on regions close to launch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
(30 reference statements)
1
14
0
Order By: Relevance
“…References [34,72] evidenced heat loads on Tore Supra ICRF antenna limiters due to fast ion losses from the plasma core. Resonant wave modes [73], wave-filament bound states [74], RF power absorption at the peripheral LH resonance [75] and ponderomotive forces [76] have been proposed in the literature, the latter especially in the vicinity of ICRF antennas. These additional processes likely exist but have not been clearly evidenced in experiments.…”
Section: Other Rf-induced Edge Processesmentioning
confidence: 99%
“…References [34,72] evidenced heat loads on Tore Supra ICRF antenna limiters due to fast ion losses from the plasma core. Resonant wave modes [73], wave-filament bound states [74], RF power absorption at the peripheral LH resonance [75] and ponderomotive forces [76] have been proposed in the literature, the latter especially in the vicinity of ICRF antennas. These additional processes likely exist but have not been clearly evidenced in experiments.…”
Section: Other Rf-induced Edge Processesmentioning
confidence: 99%
“…The rfSOL code [13], the LPP code [14] (in reference to Laboratory for Plasma Physics in Brussels) and our SSWICH code follow the second strategy and for simplicity drop the harmonics of the RF frequency. The rfSOL code mainly solves the wave propagation in presence of RF sheaths similar to Jenkins and Smithe [11].…”
Section: Specifications and Main Technical Choices In Comparison Withmentioning
confidence: 99%
“…In addition to the RF convection, the ponderomotive force can also play an important role in reshaping the final density profiles [25,26]. It is found that the ponderomotive effects are typically small for AUG L-mode plasma parameters and is not considered in this work.…”
Section: Solmentioning
confidence: 99%